Structure, histochemistry, ultrastructure and seasonal variations of the male prostatic complex in the black Myotis bat, Myotis nigricans (Chiroptera: Vespertilionidae) - Negrin, Ana C. [UNESP]; Beguelini, Mateus R. [UNESP]; Puga, Cintia C. I. [UNESP]; Christante, Caroline M. [UNESP]; Bueno, Larissa M. [UNESP]; Morielle-Versute, Eliana [UNESP]; Vilamaior, Patricia S. L. [UNESP]; Taboga, Sebastiao R. [UNESP] (Csiro Publishing, 2014)
Chiroptera are one of the most diverse orders of mammals and a unique group within Mammalia that posses a wide geographic distribution and considerable variability in reproductive strategies. The aims of the present study were to characterise the male prostatic complex of the bat Myotis nigricans (Vespertilionidae) and evaluate seasonal variations in the prostatic complex of M. nigricans specifically. Twenty-three sexually mature specimens (four sample groups: winter, spring, summer and autumn) were subjected to macroscopic, microscopic, morphometric and ultrastructural analyses. The reproductive accessory glands of M. nigricans were found to be composed of a multilobed complex associated with the urethra and a pair of inguinal bulbourethral glands. The complex was composed of three bilobed prostatic regions (ventral, dorsolateral and dorsal) with no ampullary gland and seminal vesicles. This pattern of lobulation is very similar to that described for the prostate of rodents; however, it differs from that of other mammals and even other families of bats (e.g. Phyllostomidae and Molossidae). Each prostatic region in M. nigricans has unique and distinctive characteristics, which synchronise to establish the main reproductive peak of the species in summer. The data also indicated an asynchrony in the activity of primary and secondary reproductive organs in the annual reproductive cycle of M. nigricans in SAo Paulo State, Brazil.
Keywords: asynchronous activity; prostate; reproduction